The Association Between ABO and Rhesus Blood Groups and Diabetes Mellitus in Libya: A Systematic Review of National Evidence (Razi Medical Journal, 2025)
The potential association between ABO/Rh blood groups and diabetes mellitus (DM) susceptibility remains a topic of global epidemiological interest, with population-specific findings. This systematic review aims to synthesize and analyze all available evidence on the distribution of ABO and Rh blood groups among diabetic patients across all cities in Libya to determine any consistent national pattern or association. A systematic search was conducted for studies published between 2010 and 2024. Electronic databases (PubMed, Google Scholar, Scopus) and Libyan journal archives were searched. Keywords included "ABO blood group," "Rhesus factor," "diabetes mellitus," "Libya," and specific city names. Observational studies reporting ABO/Rh frequencies in Libyan diabetic patients and controls were included. Data on study characteristics, blood group distribution, and odds ratios were extracted. Four studies from four major Libyan cities (Tripoli, Benghazi, Zliten, Zintan) met the inclusion criteria, encompassing 2,819 participants (1,919 diabetic patients and 900 controls). The pooled prevalence of blood group O was highest in both cases and controls. A meta-analysis of the pooled data revealed a significant association between blood group B and DM (OR: 1.52, 95% CI: 1.24-1.86, p < 0.001). Studies from Tripoli and Benghazi individually reported this significant association, while studies from Zliten and Zintan did not. No significant association was found between Rh factor and DM risk (OR: 1.08, 95% CI: 0.82-1.42, p = 0.59). This first systematic review from Libya indicates a potential national-level association between blood group B and an increased risk of diabetes mellitus. The lack of significance in two smaller studies highlights the need for larger, standardized, multi-center national research to confirm this finding and explore underlying genetic and environmental modifiers. The ABO blood group could be considered a modest genetic risk marker in the Libyan population.
Keywords: ABO Blood-Group System; Rhesus Factor; Diabetes Mellitus; Systematic Review; Libya; Epidemiology; Genetic Predisposition to Disease.